Solve for y 2y-9=2(y+3)

Math
2y-9=2(y+3)
Simplify 2(y+3).
Tap for more steps…
Apply the distributive property.
2y-9=2y+2⋅3
Multiply 2 by 3.
2y-9=2y+6
2y-9=2y+6
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 2y from both sides of the equation.
2y-9-2y=6
Combine the opposite terms in 2y-9-2y.
Tap for more steps…
Subtract 2y from 2y.
0-9=6
Subtract 9 from 0.
-9=6
-9=6
-9=6
Since -9≠6, there are no solutions.
No solution
Solve for y 2y-9=2(y+3)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top